Measuring consumer well-being from using zero price digital services: The case of navigation apps and location-based services - Maciej Sobolewski (European Commission, Joint Research Centre (JRC), 2021)
Digital maps and navigation applications are considered an essential tool by 70% of smartphone users. As these apps come predominantly free of charge, their contribution to consumer well-being cannot be captured by the common economic measures, like the GDP. This study demonstrates how the discrete choice experiment approach can be applied to measure, in an economically consistent way, consumer surplus from a navigation service. We elicit preferences for a satellite navigation with the two optional location-based functionalities: real-time traffic information and location-sensitive commercial information. In the experiment, the respondents are confronted with a range of location-sharing conditions set by a navigation provider. Finally, we estimate a demand model and derive welfare measures from the collected choices. Median consumer surplus from using basic satellite navigation without location-based functionalities is estimated at 8.06 EUR per month. Adding location-based services can increase this gain by 36% to 10.98 EUR, provided that users maintain control over location disclosure. Location-sharing terms set by a provider and privacy concerns of users both affect the size of the surplus from a navigation service.
Keywords: C25; D12; L51; 330; zero price digital goods; navigation; digital maps; choice experiment; consumer surplus; location